2022
DOI: 10.22190/fume220118004h
|View full text |Cite
|
Sign up to set email alerts
|

Forced Nonlinear Oscillator in a Fractal Space

Abstract: A critical hurdle of a nonlinear vibration system in a fractal space is the inefficiency in modelling the system. Specifically, the differential equation models cannot elucidate the effect of porosity size and distribution of the periodic property. This paper establishes a fractal-differential model for this purpose, and a fractal Duffing-Van der Pol oscillator (DVdP) with two-scale fractal derivatives and a forced term is considered as an example to reveal the basic properties of the fractal oscillator. Utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…As Deng and Ge [21] pointed out, He-Laplace method has a simple and reliable algorithm and it can be coupled with the HPM or the VIM for solving various nonlinear models, shedding a bright light on fractal calculus. A newest typical example of He-Laplace method to illustrate its simplicity, directness, strength, and great prospects can be found in [22]. In what follows, we employ the local fractional version of He-Laplace method [23] to solve the local fractional IDE (4).…”
Section: He-laplace Methods and Comparisonmentioning
confidence: 99%
“…As Deng and Ge [21] pointed out, He-Laplace method has a simple and reliable algorithm and it can be coupled with the HPM or the VIM for solving various nonlinear models, shedding a bright light on fractal calculus. A newest typical example of He-Laplace method to illustrate its simplicity, directness, strength, and great prospects can be found in [22]. In what follows, we employ the local fractional version of He-Laplace method [23] to solve the local fractional IDE (4).…”
Section: He-laplace Methods and Comparisonmentioning
confidence: 99%
“…In the field of composites, Zuo et al [12] used the two-scale fractal theory, and suggested the fractal laws for the electrical conductivity of graphene, carbon nanotubes and graphene/SiC composites. In the field of fractal vibration system, He et al [13] established a fractaldifferential model and a fractal Duffing-Van der Pol oscillator with two-scale fractal derivatives and a forced term was considered as an example to reveal the basic properties of the fractal oscillator. It was revealed that the exciting external force parameter plays a destabilizing role.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various devices have been developed for energy harvesting, such as the nanofluids ( He and Elazem, 2022 ), the spring-pendulum systems ( Wu et al, 2018 ; He et al, 2022a ), and the low-frequency vibration systems ( Zhang and Cai., 2012 ; He C.-H. et al, 2021 ; He et al, 2022b ). In addition to the abovementioned methods, the nanotechnology for solar energy harvesting ( Satharasinghe et al, 2020 ) is totally new and is quite promising.…”
Section: Introductionmentioning
confidence: 99%